DOMESTIC TOURIST PREFERENCES FOR SUSTAINABLE RURAL TOURISM PACKAGES: TRADE-OFFS AMONG PRICE, CARBON FOOTPRINT, AND LOCAL COMMUNITY PARTICIPATION - Sri Wahyuni; Joao Muni (Jurnal Pariwisata Tawangmangu, 2026)
This study investigates domestic tourist preferences for sustainable rural tourism packages by examining trade-offs among price, carbon footprint, and local community participation. The research is important because domestic tourism plays a strategic role in supporting regional economic resilience, while sustainability challenges require tourism products that balance economic, environmental, and social values. Data were collected through a structured survey involving 300 domestic tourists from different generational groups (X, Y, and Z) in several rural tourism destinations in Yogyakarta, Indonesia. A conjoint design was developed using 18 stimulus profiles and 4 holdout cases based on three attributes: price, carbon footprint reduction, and forms of local participation. Data were analyzed using Conjoint Analysis with Hierarchical Bayes Estimation to estimate individual preferences, followed by market simulation and cluster analysis to identify preference segments. The results indicate that price remains an important determinant, but environmental attributes and community-based activities significantly influence tourist choices, particularly among younger generations. The findings suggest that sustainable tourism packages should combine affordable pricing with visible environmental actions and authentic local engagement. Future research is recommended to include broader destination coverage and additional behavioral variables affecting sustainable travel decisions.